2017
DOI: 10.1017/s0305000917000368
|View full text |Cite
|
Sign up to set email alerts
|

Disfluencies signal reference to novel objects for adults but not children

Abstract: Speech disfluencies can guide the ways in which listeners interpret spoken language. Here, we examined whether three-year-olds, five-year-olds, and adults use filled pauses to anticipate that a speaker is likely to refer to a novel object. Across three experiments, participants were presented with pairs of novel and familiar objects and heard a speaker refer to one of the objects using a fluent ("Look at the ball/lep!") or disfluent ("Look at thee uh ball/lep!") expression. The salience of the speaker's unfami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…Our study provides an important contribution to the literature on children's predictive use of disfluencies, which had previously been limited to studies of monolingual English-learning children (Kidd et al, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens et al, 2018;Thacker, Chambers, & Graham, 2018). We replicated these findings with English monolinguals, and extended them to French monolinguals and French-English bilinguals.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our study provides an important contribution to the literature on children's predictive use of disfluencies, which had previously been limited to studies of monolingual English-learning children (Kidd et al, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens et al, 2018;Thacker, Chambers, & Graham, 2018). We replicated these findings with English monolinguals, and extended them to French monolinguals and French-English bilinguals.…”
Section: Discussionsupporting
confidence: 64%
“…The sequence of each trial followed Kidd et al (2011), such that novel labels were also discourse-new (see Graham, 2016, andOwens et al, 2018, for evidence that discourse novelty is a driver of disfluency effects in children). There were three presentations of each object label.…”
Section: Stimulimentioning
confidence: 99%
“…As the discourse-new object was also always the novel object in the Kidd et al (2011) paradigm, a recent series of studies sought to disentangle these factors. These findings demonstrated that 2- and 3-year-old children readily associate filled pauses with upcoming reference to discourse-new ( Owens and Graham, 2016 ) objects but not unfamiliar objects ( Owens et al, 2017 ). This contrasts with studies showing that adults show referential anticipation of novel objects upon hearing a filled pause ( Arnold et al, 2007 ; Owens et al, 2017 ).…”
Section: Introductionmentioning
confidence: 80%
“…These findings demonstrated that 2- and 3-year-old children readily associate filled pauses with upcoming reference to discourse-new ( Owens and Graham, 2016 ) objects but not unfamiliar objects ( Owens et al, 2017 ). This contrasts with studies showing that adults show referential anticipation of novel objects upon hearing a filled pause ( Arnold et al, 2007 ; Owens et al, 2017 ). Recently, research has highlighted preschoolers’ ability to amend an initial prediction (e.g., that talkers are more likely to refer to a preferred familiar object) when encountering a disfluency ( Thacker et al, 2018 ).…”
Section: Introductionmentioning
confidence: 80%
“…Recordings of participants' eye movements showed that listeners already anticipated reference to unknown objects (increase in proportion of fixations to unknown objects) when hearing the filler uh in the disfluent condition (i.e., well before hearing the target). Other studies have since shown the same effect in children as young as 2 years of age (Kidd, White, & Aslin, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens, Thacker, & Graham, 2018;Thacker, Chambers, & Graham, 2018a, 2018b. Adult listeners have also been shown to be able to predict other types of complex referents, such as discourse-new (Arnold, Fagnano, & Tanenhaus, 2003;Arnold, Tanenhaus, Altmann, & Fagnano, 2004;Barr & Seyfeddinipur, 2010), compound (Watanabe, Hirose, Den, & Minematsu, 2008), and low-frequency referents (Bosker, Quené, Sanders, & De Jong, 2014a) upon hearing a disfluent filler uh.…”
mentioning
confidence: 86%